1989
DOI: 10.1177/0887302x8900800102
|View full text |Cite
|
Sign up to set email alerts
|

Buying For the Small Apparel Retail Store: Job Content Across Four Merchandise Categories

Abstract: The success of a retail store is dependent upon the skills and knowledge of the buyer. The purposes of this study were to investigate the job content of buyers in small apparel stores and to compare specific job elements across four merchandise categories: a) men's apparel, b) women's apparel, c) children's apparel, and d) accessory and other apparel. MANOVA was used to compare six divisions of worker-oriented job elements across the four merchandise categories and to test for differences between the variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…This was the third most often listed competency by the buyers. The high level of importance placed on this competency by all three groups is consistent with findings by Fiorito and Fairhurst (1989), who determined that customers were an important element in the buying function for small retailers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was the third most often listed competency by the buyers. The high level of importance placed on this competency by all three groups is consistent with findings by Fiorito and Fairhurst (1989), who determined that customers were an important element in the buying function for small retailers.…”
Section: Discussionsupporting
confidence: 89%
“…Appliance buyers, however, stated that brand name was more important than fashionability in their buying responsibilities. Fiorito and Fairhurst (1989) investigated the job content of buyers in small apparel stores. Judging quality, decision making, consumer behavior, and attention to detail were rated as most important/frequently used job components by these buyers.…”
mentioning
confidence: 99%
“…Francis and Brown (1985) found differences between apparel and appliance buyers, and Fiorito and Fairhurst (1989) found differences between small store buyers in different merchandise categories. Francis and Brown (1985) found differences between apparel and appliance buyers, and Fiorito and Fairhurst (1989) found differences between small store buyers in different merchandise categories.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research has been published focusing on apparel retail buyers (e.g., Anthony & Jolly, 1991;Fairhurst & Fiorito, 1990;Fiorito & Fairhurst, 1989;1993;Shim & Kotsiopulos, 1991; Stemquist, Tolbert, & Davis, 1989;Tolbert, Stemquist, & Davis, 1988). For example, both survey research (Fairhurst & Fiorito, 1990;Shim & Kotsiopulos, 1991) and experimental research (Wagner, Ettenson, & Parrish, 1989) have addressed vendor (manufacturer) selection by retail buyers.…”
Section: Related Literaturementioning
confidence: 99%
“…For example, both survey research (Fairhurst & Fiorito, 1990;Shim & Kotsiopulos, 1991) and experimental research (Wagner, Ettenson, & Parrish, 1989) have addressed vendor (manufacturer) selection by retail buyers. Research examining the job content of apparel retail buyers has indicated that buying for a small store is more diversified than buying for a large store (Fiorito & Fairhurst, 1989). As compared to a buyer from a large store, a buyer for a small store must establish relationships with many more manufacturers' sales representatives in order to procure the merchandise assortment necessary for a small store (Fiorito & Fairhurst, 1989).…”
Section: Related Literaturementioning
confidence: 99%